2000
DOI: 10.1063/1.1286035
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation in glassforming liquids and amorphous solids

Abstract: The field of viscousliquid and glassysolid dynamics is reviewed by a process of posing the key questions that need to be answered, and then providing the best answers available to the authors and their advisors at this time. The subject is divided into four parts, three of them dealing with behavior in different domains of temperature with respect to the glass transition temperature, Tg,and a fourth dealing with "short time processes. " The first part tackles the high temperature regime T>Tg, in which the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,876
3
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 2,108 publications
(1,962 citation statements)
references
References 362 publications
47
1,876
3
6
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Thus it has been shown that strongly correlating viscous liquids to a good approximation have all eight frequency-dependent thermoviscoelastic response functions [19][20][21] given in terms of just one 22 (i.e., are single-parameter liquids in the sense of having dynamic Prigogine-Defay ratio 19 close to unity 2,20,22 ). Strongly correlating viscous liquids moreover obey density scaling [23][24][25][26][27] to a good approximation, i.e., their dimensionless relaxation timeτ ≡ τρ 1/3 √ k B T /m (where m is the average particle mass) depends on density ρ = N /V and temperature as τ = F(ρ γ /T ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the stability of the amorphous phases and to ensure that no structural relaxations are present, as mentioned by Angell et al, 44 we subjected the simulation cells to a quasi-static thermal cycle, in which the system was equilibrated at a range of (first increasing, then decreasing) temperatures. In Fig.…”
Section: A Rdfs and The Glassy Phasementioning
confidence: 99%
“…For a review, see (Angell et al, 2000;Böhmer et al, 1993). A specific example of a τ (T ) dependence is shown in the l.h.s.…”
Section: Overview Of the Classical Theory Of The Structural Glassmentioning
confidence: 99%